CD44-Targeted Hyaluronic Acid Nanoparticles for Triple-Negative Breast Cancer: Recent Advances and Clinical Perspectives - Sirajunisa Talath (Probecell Science, 2026)
Triple-negative breast cancer (TNBC) is a tough, heterogeneous subtype of breast cancer characterised by the absence of oestrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 expression, which results in limited therapeutic options and bad clinical outcomes. Several nanomedicine strategies based on the use of hyaluronic acid (HA)-based nanoparticles have attracted a great deal of attention due to their biocompatibility, biodegradability and the intrinsic affinity toward the CD44 receptor expressed in TNBC cells and breast cancer stem cells. They can offer selective drug delivery targeted at tumour cells through CD44, increase enrichment of drugs in the tumour tissue, overcome multi-drug resistance, and modify the tumour microenvironment, providing increased therapeutic efficacy and reduced systemic toxicity. This review summarises the current advances in designing, engineering and therapeutic applications of CD44-targeted hyaluronic acid nanocarrier for triple-negative breast cancer. We also discuss preclinical findings, clinical challenges, and present and future directions for the development of precision nanomedicines designed to improve outcomes for patients with TNBC.